Digital Government (A Study of the Value of Usefulness and Technology Adoption in the Regional Development Information System/SIPD of Palopo City) - Wiwi, Wiwi; Andi Cudai Nur; Andi Anugrah Mahyuddin (Universitas Negeri Makassar, 2024)
This study aims to analyze the implementation process of the Family Hope Program (Program Keluarga Harapan, PKH) in Alla District and assess its impact on community welfare. Utilizing a qualitative approach, data collection techniques included observations, interviews, and documentation. The data analysis process involved data reduction and presentation to derive meaningful insights. The findings indicate that the implementation of PKH in Alla District significantly enhances the welfare of impoverished families, particularly in fulfilling their educational, health, and economic needs. The program alleviates the financial burdens faced by Beneficiary Families (Keluarga Penerima Manfaat, KPM) and improves their access to essential health services through the Healthy Indonesia Card (Kartu Indonesia Sehat, KIS). The success of the PKH program is contingent upon several factors, including the accuracy of beneficiary data, effective coordination among stakeholders, and robust management practices. Despite its positive outcomes, the study identifies several challenges that could hinder the program's sustainability. These challenges include the limited number of facilitators available to support KPM and the necessity for a structured graduation process for beneficiaries. Addressing these issues is crucial to ensure that the program not only continues to provide immediate assistance but also fosters long-term economic independence among beneficiaries. Overall, the PKH program has a profound impact on improving community welfare, particularly for KPM, by facilitating access to education, healthcare, and economic resources. It plays a vital role in easing the economic strain on families, especially in financing children's education and healthcare needs. The role of PKH facilitators is critical in ensuring that the assistance provided is utilized effectively. While the direct economic benefits of the program are evident, it is essential to tackle the existing challenges to enhance the program's sustainability and promote the economic self-sufficiency of KPM in the long run.